2002
DOI: 10.2117/psysoc.2002.176
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Study of Organizational Commitment, Self-Efficacy and Psychological Barriers to Technological Change

Abstract: Relationship among organizational commitment, self-efficacy and perceived psychological barriers to technological change was studied in a sample of 167 male managers selected from Tata Engineering and Locomotive company, Jamshedpur, Jharkhand, India. Organizational Commitment Scale developed by Allen and Meyer (1990), Generalized Perceived Self-efficacy Scale by Schwarzer and Jerusalem (1995), Questionnaire to measure Psychological Barriers to Technological Change by Ghani and Sugumar (1999) were the tools. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(20 reference statements)
1
14
0
2
Order By: Relevance
“…Shahnawaz & Jafri (2009) [50] have done a research using public and private organizations in India and found that slight positive relationship between PsyCap and OC among the managers. Sinha, Talwar, and Rajpal (2002) [51] stated that there was a positive relationship between self-efficacy and OC in a sample of 167 managers. Larson & Luthans (2006) with their exploratory study in small factory found that positive relationship between the level of PsyCap of production worker and their OC [47].…”
Section: Psycap Work Attitudes and Job Performancementioning
confidence: 99%
“…Shahnawaz & Jafri (2009) [50] have done a research using public and private organizations in India and found that slight positive relationship between PsyCap and OC among the managers. Sinha, Talwar, and Rajpal (2002) [51] stated that there was a positive relationship between self-efficacy and OC in a sample of 167 managers. Larson & Luthans (2006) with their exploratory study in small factory found that positive relationship between the level of PsyCap of production worker and their OC [47].…”
Section: Psycap Work Attitudes and Job Performancementioning
confidence: 99%
“…The different dimensions of PsyCap have been shown to have a positive correlation with organisational commitment (Luthans, Norman, Avolio & Avey, 2008). Empirical research has found that organisational commitment is correlated with hope, optimism, resilience and self-efficacy (Sinha, Talwar & Rajpal, 2002;Youssef & Luthans, 2007). Buys and Rothmann (2010) reported a positive correlation between organisational commitment and work engagement, concluding that engaged employees had better social functioning and affective commitment.…”
Section: Relationship Between Constructsmentioning
confidence: 99%
“…In a study by McColl-Kennedy and Anderson (2005), there was evidence of a dependency link between optimism and commitment [57]. Sinha, Talwar, and Rajpal (2002) studied the relationship between self-efficacy and organizational commitment and found that organizational commitment is positively related with self-efficacy [37].…”
Section: Relationship Between Psychological Capital and Organisationamentioning
confidence: 99%
“…provide interventions that specifically target hope, self efficacy, resilience and optimism in the employees. Research has shown that psychological resource capacities do have a positive impact on organisational commitment [31,37].Individuals with higher positive affect express more positive states and develop positive measurable actions in the personal and social relationship in comparison with individuals with lower positive affect [58].…”
Section: Psychological Capital a Predictor Of Organisational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation